2020
DOI: 10.1016/j.aninu.2020.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Dietary supplementation of yeast cell wall improves the gastrointestinal development of weaned calves

Abstract: The purpose of this study was to investigate the potential benefits of yeast cell wall (YCW) on the gastrointestinal development of weaned calves. Twenty healthy Holstein male calves (BW = 92 ± 8.29 kg and 60 ± 5 d of age) were randomly allocated into 2 groups: CON with no YCW, and YCW (accounted for 0.16% of the basal diet). The dietary concentrate-to-roughage ratio was 40:60. All the calves were fed regularly twice a day at 09:00 and 16:00 and had free access to water. The experiment lasted for 60 d. The res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 31 publications
0
24
0
1
Order By: Relevance
“…Additionally, increases in villus height and crypt depth, both measures of intestinal health, have been found in weaned pigs supplemented with yeast [ 16 ]. In weaned dairy calves, YCW supplementation improved the development of the GI tract [ 17 ]. The combination of yeast ( Saccharomyces cerevisiae ) and the probiotic Bacillus licheniformis reduced the permeability of the small intestine in pigs challenged with Escherichia coli K88, demonstrating improved intestinal integrity and barrier function [ 18 ].…”
Section: Yeast Productsmentioning
confidence: 99%
“…Additionally, increases in villus height and crypt depth, both measures of intestinal health, have been found in weaned pigs supplemented with yeast [ 16 ]. In weaned dairy calves, YCW supplementation improved the development of the GI tract [ 17 ]. The combination of yeast ( Saccharomyces cerevisiae ) and the probiotic Bacillus licheniformis reduced the permeability of the small intestine in pigs challenged with Escherichia coli K88, demonstrating improved intestinal integrity and barrier function [ 18 ].…”
Section: Yeast Productsmentioning
confidence: 99%
“…Moreover, supplementing above yeast feed continuously at 100 mg/kg could enhance the overall feed efficiency by 21 point in challenged turkeys. In addition, plentiful researches displayed that yeast culture and yeast cell wall components showed positive effects on growth performance in different animals ( Gao et al., 2008 ; Ma et al., 2020 ; Sun et al., 2020 ). The beneficial effects of YC-EHY on growth performance of broiler chickens might be due to that the yeast-derived additive or its components could improve health responses, immune, and anti-inflammatory effects in animals, as previously reported ( Salinas-Chavira et al., 2018 ; Silva et al., 2018 ; Bu et al., 2020 ).…”
Section: Disscusionmentioning
confidence: 99%
“…(2008) showed that the balance between anti-inflammatory and proinflammatory cytokines is important in SIgA and IgG productions. Thus, researchers showed that supplementing yeast-derived products could decrease the mRNA expression levels of intestinal proinflammatory genes, thereby improving intestinal barrier function and immune status in animals ( Alizadeh et al., 2016 ; Wang et al., 2016b ; Li et al., 2017 ; Ma et al., 2020 ), which probably indirectly promoted the production of immunoglobulin. Interestingly, Lessard et al.…”
Section: Disscusionmentioning
confidence: 99%
See 1 more Smart Citation
“…Calves are the future of beef cattle farming, and this stage is vital to the production performance of beef cattle in the future. Early weaning of calves can improve the reproductive performance of adult cattle and speed up the ruminal development of calves ( Ma et al., 2020 ). In recent years, early weaning was commonly conducted in rearing calves of commercial beef cattle farms.…”
Section: Introductionmentioning
confidence: 99%